Fragmentation analysis of optimized blasting rounds in the Aitik mine : effect of specific charge - Demenegas, Vasileios (2008)
This report investigates the effect increased specific charge has on the fragment size distribution of the blasted material. It is a part of a related project of the Swedish blasting research center named “Model for bench blasting in open pits” and the field tests took place in Boliden’s Aitik copper mine in Gällivare. The goal of this thesis work was to measure the difference in fragmentation caused due to increased specific charge. In order to achieve this, one bench i.e. bench 5162, was divided into two blasting domains. One domain was charged with the normal specific charge used for bench blasting in the mine which is approximately 1 to 1.1 kg/cu.m., while the other domain had a slightly elevated specific charge close to 1.35 kg/cu.m. A combination of optical methods and lab sieving tests was used to evaluate the fragment size distribution of the blasted material in each blasting domain. The software used for the purposes of this investigation is “Split Desktop”. Over 250 images of truck – loads were acquired during the loading period of the material, from which, 60 were picked according to a quality criterion formulated and analyzed with the afore-mentioned software suite. In addition to the image analysis, four samples were taken from the muck pile, two from each blasting domain and they were sent for sieving in an accredited laboratory. A compilation of image analysis and laboratory sieving data was used in an attempt to describe the fragment size distribution curve for the material within each blasting domain with the use of the Swebrec function incorporated in the KCO model. The results were satisfactory with the Swebrec function obtaining a fit better than 0.999 for both domains. Included in the field work was detailed monitoring of the drilling and charging parameters. The results, along with additional information provided by the mine personnel, were used in order to obtain the fragment size distribution estimation of different theoretical models for each blasting domain. For the last part of the ...